Precipitation records of anthropogenic nitrogen pollution in two metropolitan cities of Southeast Asia - Zhang, Kun (2024)
Human activities have promoted a rapid and continuous increase in atmospheric nitrogen (N) emission and deposition, resulting in a series of ecological and environmental problems. However, our understanding of N deposition in densely populated tropical regions remains limited, particularly regarding the chemical composition, historical changes, and its association with human activities. In this research, we aim to address these gaps by analyzing concentrations of nitrate (NO3−), ammonium (NH4+) and dissolved organic N (DON) in daily precipitation samples collected in Singapore and Ho Chi Minh City, Vietnam between May 2019 and April 2020. Results reveal that wet N deposition in Singapore and Ho Chi Minh City averaged 31.3 and 30.4 kg N ha−1 yr−1, respectively. Compared to 2001 record, wet N deposition fluxes in Singapore and Hanoi, Vietnam have increased by an average of 78% and 87%, respectively, between 2001 and 2020. Emission data strongly indicate that fossil fuel combustion has significantly elevated both fluxes and chemical composition changes of N deposition in Vietnam. This study provides important observation data of N deposition in tropical urban areas, aiding the assessment of regional N pollution and the management of anthropogenic N emissions in densely populated tropical regions.